Collaborative Governance: Lampung Province Promotional Tourism Promotion based on Digital Media - Miswwan Gumanti; Bernadhita H. S. Utami; Rita Irviani; Fauzi Fauzi (Prosiding International conference on Information Technology and Business (ICITB), 2019)
The tourism sector is able to provide large revenues to the regional and state treasury. Tourism in Indonesia has an important role in increasing the country's foreign exchange as an attraction for foreign tourists coming to the country and stakeholders pay attention to the progress of tourism in Indonesia. After the implementation of decentralization in every region of Indonesia, it gives flexibility to manage their own households. Pesawaran Regency, Lampung Province is one of the areas that is currently experiencing a change from the tourism sector which is very promising to increase Regional Original Revenue and public welfare with various promotional efforts through the development of the digital era which is very rapid. From the results of the study show: the role of local government collaborative governance of tourism promotion through digital society Pesawaran, Lampung provides a very large contribution to the development in the area of regional tourism, this condition is seen from the number of visits to local tourism and hotel guests available in Bandar Lampung. Almost all Hotels in Bandar Lampung collaborate with local tourism objects to provide services to tourists to the tourist attractions in Pesawaran, Lampung. Tourism promotion is inseparable with the important role of the digital era, widely available in Electronic Commerce. One of the authorities of local governments in the provisions of Law No. 10 of 2009 concerning Tourism. The position of the Regional Tourism Promotion Board is as a regional government partner in developing and determining tourism promotion policy strategies between the central and regional governments and coordinating in the tourism sector.Keywords: collaborative governance; tourism; digital era; Pesawaran